Evaluation of the New MB Redox System for Detection of Growth of Mycobacteria - Cambau, Emmanuelle (American Society for Microbiology, 1999)
We evaluated a new mycobacterial culture system, MB Redox, for recovery rate and time to detection of mycobacteria from 742 consecutive respiratory specimens and compared the results to those found with Löwenstein-Jensen (LJ) medium. Twenty specimens (2.7%) were positive for M. tuberculosis: 17 on LJ medium and 19 in MB Redox, with 16 specimens positive in both media. In addition, 24 specimens (3.2%) were positive for nontuberculous mycobacteria (NTM), 20 on LJ medium, 18 in MB Redox, and 14 in both media. For M. tuberculosis, the mean times to detection were 28.9 days on LJ medium and 23.6 days in MB Redox, and for NTM, the mean times to detection were 40.6 days on LJ medium and 32.3 days in MB Redox.